2022
DOI: 10.30934/kusbed.1136101
|View full text |Cite
|
Sign up to set email alerts
|

Kinesiophobia, Physical Activity, Depression, Anxiety and Stress Levels in Post COVID-19 Individuals: A Cross-Sectional Study

Abstract: Objective: Kinesiophobia, inactivity and mood disturbances in post-COVID-19 individuals are poorly investigated. Therefore, the aim of this study was to compare measures of kinesiophobia, physical activity, depression, anxiety and stress in post-COVID-19 individuals and healthy individuals. Methods: This cross-sectional study was conducted between 25 November 2021 and 30 December 2021. The individuals were recruited from the general community. Kinesiophobia was assessed with the Tampa Scale of Kinesiophobia, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…Consistent with the results of this study, although high levels of kinesiophobia were reported in some of the adolescent volleyball players with and without post-COVID-19 in our study, kinesiophobia scores were similar between our groups. The kinesiophobia scores were found to be higher in adult individuals with post-COVID-19 compared to healthy adults who were evaluated in the second year of the pandemic [3,4]. Contrary to the results of these studies, in our study, no difference was found in terms of kinesiophobia scores in adolescent volleyball players with and without post-COVID-19.…”
Section: Resultscontrasting
confidence: 98%
See 3 more Smart Citations
“…Consistent with the results of this study, although high levels of kinesiophobia were reported in some of the adolescent volleyball players with and without post-COVID-19 in our study, kinesiophobia scores were similar between our groups. The kinesiophobia scores were found to be higher in adult individuals with post-COVID-19 compared to healthy adults who were evaluated in the second year of the pandemic [3,4]. Contrary to the results of these studies, in our study, no difference was found in terms of kinesiophobia scores in adolescent volleyball players with and without post-COVID-19.…”
Section: Resultscontrasting
confidence: 98%
“…No statistically significant difference was found between the groups when the kinesiophobia, dyspnea, pain and fatigue felt at rest and during activities, depression, stress, static and dynamic balance scores of the volleyball players were compared ( No statistically significant differences were found in the rates of high degree of kinesiophobia, dyspnea, pain, and fatigue at rest and during activities, depression, anxiety, and stress (Table In the COVID-19 pandemic, the incidences of physical inactivity and kinesiophobia, defined as the fear of movement, have increased in individuals due to mandatory restrictions and quarantine rules [2][3][4]. It has been found that the kinesiophobia scores were similarly higher in elderly individuals with and without COVID-19 [2].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher kinesiophobia levels are associated with decreased physical activity (35). Studies have also shown that older men with post-COVID-19 sarcopenia experienced kinesiophobia (36,37).…”
Section: Discussionmentioning
confidence: 99%